The interrelationship between ignorance processors is ideologically defined and strategic achievement achieved - عبدعلي لمياء سلمان; مهدي حنان حسين (Journal of Economics and Administrative Sciences, 2019)
Abstract : The aim of the study is to diagnose the level and nature of the relationship between cognitive interactions, cognitive ignorance and the achievement of strategic excellence). The aim of this is to explore theoretical philosophy and intellectual implications of these variables, and, then test the correlation and impact relationships and their feasibility in the application environment, which was formed from the seven directorates in the Ministry of Education. The sample of the study was determined by the directors, their assistants, and the department directors. The sample number is (130). The importance of the study is to come out with a philosophical basis for the nature of the variables, based on an applied effort for the reality of cognitive ignorance processes to achieve strategic excellence. In order to achieve this, two main hypotheses are devised, 8 sub-hypotheses. The validity of these hypotheses has been tested by a set of statistical tools. A questionnaire is used as a primary tool to collect data, and interviews are used to gather information. One of the main conclusions is that there is a link relationship with moral significance between knowledge ignorance processers, achieved strategic excellence and good attention of leaders in the Ministry of Education with the dimensions of ignorance processes, and lack of attention in dimensions of strategic excellence. Based on these conclusions the study recommends with increase the leaders’ attention in Ministry of Education with the dimensions of knowledge ignorance processes in addition to great concentration on dimension of strategic excellence